2005
DOI: 10.1007/bf02978203
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antitumor macrolides fromstreptomyces sp. Is9131

Abstract: Four compounds, including two novel macrolides, were isolated from an endophyte Streptomyces sp. Is9131 of Maytenus hookeri. Spectral data indicated that these compounds were dimeric dinactin (1), dimeric nonactin (2), cyclo-homononactic acid (3), and cyclo-nonactic acid (4). Bioassay results showed that dimeric dinactin had strong antineoplastic activity and antibacterial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…ls9131 of M. hookeri as previously reported (9), and its purity is >95%. The compound was dissolved in DMSO to the concentration of 0.1 mol/L (in vitro) or in ethanol (in vivo) before each assay and then diluted with normal saline.…”
Section: Methodssupporting
confidence: 52%
See 2 more Smart Citations
“…ls9131 of M. hookeri as previously reported (9), and its purity is >95%. The compound was dissolved in DMSO to the concentration of 0.1 mol/L (in vitro) or in ethanol (in vivo) before each assay and then diluted with normal saline.…”
Section: Methodssupporting
confidence: 52%
“…However, MFTZ-1 was cyclized to form a dimacrolide, and the substituent at C-8 ¶ was ethyl in this compound but methyl in dimeric nonactic acid. Dimeric nonactic acid did not show obvious antifungal or antibacterial activity; however, the dimeric dinactin showed strong antibacterial activity (9). Overall, it seems that the lactone ring may play an important role in these activities.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…[1,2] In the course of our exploration for chemical constituents from the endophytic microorganisms of medicinal plants, a series of new compounds were isolated previously. [3][4][5][6][7] Camptotheca acuminate, a medicinal plant specifically distributed in China, is rich in the anticancer compound camptothecin, with the highest distribution in the new leaf of up to 0.4 %. In such a special living environment, special endophytic fungi may exist.…”
Section: Introductionmentioning
confidence: 99%
“…maytansine) from endophytic microorganisms residing in Maytenus hookeri (Celastraceae), has shown that the culture material of some Streptomyces sp. on M. hookeri contained compounds that exhibited potent activities against several pathogenic micro-organisms (Zhao et al 2005) and also had antineoplastic activity (Lu and Shen 2003).…”
Section: Introduction*mentioning
confidence: 99%